2013
DOI: 10.1002/pen.23746
|View full text |Cite
|
Sign up to set email alerts
|

Thoughening of poly(lactic acid) with silicone rubber

Abstract: In this study, poly(lactic acid) (PLA) was blended with silicone rubber (SR) to improve its impact strength and toughness by using dynamic crosslinking in the presence of peroxide during melt compounding. The SR to PLA ratio, peroxide and coagent concentrations were taken as experimental parameters. Blends were evaluated in terms of their thermal properties, tensile and impact strengths, dynamic mechanical properties, and micro‐structure. Results showed that PLA was successfully toughened with SR using dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[99,100] PLA has been employed in biomedical applications such as bone screws, sutures and tissue engineering scaffolds. [32,71,[101][102][103][104] Synthetic biodegradable materials such as PLA, poly-glycolic acid (PGA), and poly-caprolactone (PCL), along with their copolymers, are used in biomedical devices since they are biocompatible. In general, PLLA is widely used in the biomedical field due to its biodegradability, biocompatibility, thermal plasticity and its suitable mechanical properties.…”
Section: Application Of Plamentioning
confidence: 99%
“…[99,100] PLA has been employed in biomedical applications such as bone screws, sutures and tissue engineering scaffolds. [32,71,[101][102][103][104] Synthetic biodegradable materials such as PLA, poly-glycolic acid (PGA), and poly-caprolactone (PCL), along with their copolymers, are used in biomedical devices since they are biocompatible. In general, PLLA is widely used in the biomedical field due to its biodegradability, biocompatibility, thermal plasticity and its suitable mechanical properties.…”
Section: Application Of Plamentioning
confidence: 99%
“…It is a linear aliphatic thermoplastic polyester that is generally produced from lactic acid by ring‐opening polymerization . Despite its promising features, including its optical clarity, high strength and modulus, and easy processing in conventional equipment, the widespread use of PLA is limited because of its brittleness and low crystallization rate …”
Section: Introductionmentioning
confidence: 99%
“…4 Despite its promising features, including its optical clarity, high strength and modulus, and easy processing in conventional equipment, the widespread use of PLA is limited because of its brittleness and low crystallization rate. 5 Previous studies have reported the use of plasticizers for the improvement of PLA properties. [6][7][8][9] Plasticizers are widely used in the plastics industry to improve the processability, flexibility, and ductility of glassy polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In the PLA/SEBS bioblends there is a shift to the left of the T g and of the double melting peak whereas the onset of T cc remained unchanged, though the peak is broadened, indicating the SEBS dispersed phase does not act as a nucleating agent. On the other hand, Yildiz et al when studying the effect of silicon rubber (SR) on the toughening of PLA observed that SR decreased the T cc onset and peak temperature and broadened the T cc peak, acting as a nucleating agent. After thermal treatment (Figure b) there is a disappearing of the T cc of neat PLA and of PLA in the bioblends.…”
Section: Resultsmentioning
confidence: 99%